Accessing Success through the Writing Centres at a University of Technology. (1st July 2016) - Zuma, Nonhlanhla; Popoola, Tosin; Makondo, Livingstone
Abstract: University students are diverse not only in their demographics, but also in their academic literacy needs. To meet and accommodate the writing needs of all learners, writing centres were established in 2013 at a selected University of Technology (UoT). This study explored the factors that influence use of the writing centre at a selected UoT campus, using a descriptive qualitative design. The study triangulated data collected from interviews with 15 purposively recruited participants and responses from 50 consultations forms. The study findings provided insights into the academic needs of participants, factors influencing use of the writing centres and participants' evaluation of the writing centres in relation to their academic pursuit. Participants' academic literacy needs included issues with grammar, public speaking and pronunciation. Taking account of the range of needs of writing centre users at the selected UoT and the diverse factors affecting use of the writing centres, it is recommended that the writing centre invests in the continuing development of its staff so that they can be more responsive to the writing needs of its users. Furthermore, since the factors predicting use of the writing centre include personal and organizational factors, it is important that strategies to raise awareness of the writing centre be tailored appropriately to the needs of the university community.